2020
DOI: 10.1016/j.ajp.2020.102258
|View full text |Cite
|
Sign up to set email alerts
|

The wounded healer: A narrative review of the mental health effects of the COVID-19 pandemic on healthcare workers

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
4
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 14 publications
0
59
4
5
Order By: Relevance
“…In their study, increasing age, an absence of work-related troubles and being married or being a cohabitant reduced the likelihood of at least one mental health outcome. Furthermore, in a recent meta-analysis the prevalence of anxiety symptomatology, investigated in 17 studies was obtained as 31.9%, whereas the prevalence of depressive symptoms, investigated in 14 studies, was reported as 33.7% (30). While the above studies focused mainly on the general population, the currently available research suggests that frontline healthcare workers in particular have experienced increased depression and anxiety symptoms [see (31) for an overview of ten studies conducted in Asia on this topic].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, increasing age, an absence of work-related troubles and being married or being a cohabitant reduced the likelihood of at least one mental health outcome. Furthermore, in a recent meta-analysis the prevalence of anxiety symptomatology, investigated in 17 studies was obtained as 31.9%, whereas the prevalence of depressive symptoms, investigated in 14 studies, was reported as 33.7% (30). While the above studies focused mainly on the general population, the currently available research suggests that frontline healthcare workers in particular have experienced increased depression and anxiety symptoms [see (31) for an overview of ten studies conducted in Asia on this topic].…”
Section: Introductionmentioning
confidence: 99%
“…There are also increasing reports of high rates of anxiety, insomnia and depressive symptoms amongst the general public and frontline medical staff, especially during a lockdown [ 25 , 26 ]. An effective pandemic response must also include a mental health response, and GPs could be an effective part of this response.…”
Section: Provision Of Affordable Carementioning
confidence: 99%
“…First, we would like to point out that "flattening the curve" is not the only defining graphic of the Coronavirus Disease 2019 (COVID-19) pandemic but we also need to "raise the line" of our healthcare capacity. It is clear that health systems and health workers worldwide are under tremendous stress from the growing pandemic; reports of overworked healthcare staff (Ng et al, 2020) and delayed access to care (Lazzerini et al, 2020) are not uncommon. Importantly, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is dissimilar from the common flu or other coronaviruses: it is much more contagious and infected persons may remain relatively asymptomatic (Yeo et al, 2020;Wang et al, 2020).…”
Section: Letter To the Editormentioning
confidence: 99%